2022
DOI: 10.3390/cells11142176
|View full text |Cite
|
Sign up to set email alerts
|

CLL-Derived Extracellular Vesicles Impair T-Cell Activation and Foster T-Cell Exhaustion via Multiple Immunological Checkpoints

Abstract: Background: Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of malignant B-cells and multiple immune defects. This leads, among others, to severe infectious complications and inefficient immune surveillance. T-cell deficiencies in CLL include enhanced immune(-metabolic) exhaustion, impaired activation and cytokine production, and immunological synapse malformation. Several studies have meanwhile reported CLL-cell–T-cell interactions that culminate in T-cell dysfunction. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…42 It is worth noting that TEVs may induce exhaustion of CAR-T cells, impair their proliferation and anti-tumor activity. 19,[43][44][45] Specifically, the immunological checkpoints (IC) including PD-L1 found in TEVs could be responsible for the negative effect of TEVs in CAR-T cells. 19,45 Therefore, in our study, we adopted EVs derived from HEK293T cells to deliver target antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 It is worth noting that TEVs may induce exhaustion of CAR-T cells, impair their proliferation and anti-tumor activity. 19,[43][44][45] Specifically, the immunological checkpoints (IC) including PD-L1 found in TEVs could be responsible for the negative effect of TEVs in CAR-T cells. 19,45 Therefore, in our study, we adopted EVs derived from HEK293T cells to deliver target antigen.…”
Section: Discussionmentioning
confidence: 99%
“…19,[43][44][45] Specifically, the immunological checkpoints (IC) including PD-L1 found in TEVs could be responsible for the negative effect of TEVs in CAR-T cells. 19,45 Therefore, in our study, we adopted EVs derived from HEK293T cells to deliver target antigen. The HEK293T cell line is derived from human embryonic kidney cells and is frequently used in various experiments and studies associated with EVs.…”
Section: Discussionmentioning
confidence: 99%
“…EVs purified from CLL cells can also impede antitumor immune surveillance by blocking the proliferation, activation, and metabolism of T lymphocytes and promoting T cell exhaustion and the formation of regulatory T cells [ 59 ]. Böttcher et al suggested that these processes are regulated by the detection of immunological checkpoints (ICs) on CLL EVs, although a causal relationship with T cell dysregulation was not demonstrated.…”
Section: Cll Evs and Their Role In The Tmementioning
confidence: 99%
“…Two recent studies of anti-CD19 chimeric antigen receptor (CAR)-T cell therapy showed that CLL EVs can disrupt the immune synapse and contribute to the CAR-T-cell’s exhaustion, metabolic quiescence [ 59 ], or even lysis [ 86 ]. These findings might explain the CAR-T-cell treatment failure observed in the clinic.…”
Section: Clinical Implications Of Ev Biology In Cllmentioning
confidence: 99%
“… 4 Finally, it was recently shown that CLL-derived sEVs alter CD4 + and CD8 + T-cell leading to an expansion of regulatory T-cell subsets and exhaustion, respectively. 5 …”
mentioning
confidence: 99%